Использование элементной базы Active-HDL при исследовании устройств в САПР на основе K-значного дифференциального исчисления - Гладких, Т. В.; Леонов, Сергей Юрьевич (НТУ "ХПИ", 2004)
У статті розглядаються питання, які пов'язані з можливістю застосування моделей, що описані на мові VHDL для дослідження дієздібності пристроїв у системі на основі K-значного диференційного числення. Це дає можливість більш точного аналізу дієздібності пристроїв, які спроектовані раніш у середовищі Active-HDL та надає розробленій системі властивість відкритості.

In article the questions connected to an opportunity of use of models, described on language VHDL for research of serviceability of devices in system are considered on the basis of K-value differential calculus. It enables more exact analysis of serviceability of the devices designed earlier in Active-HDL environment and expands property of an openness of the developed system.
Keywords: функциональная иерархия; рекурсия; поведенческий уровень; вычислительное устройство; Active-HDL; VHDL